2020
DOI: 10.7290/tsc020102
|View full text |Cite
|
Sign up to set email alerts
|

Racial Mislabeling in Multiracial Individuals: Implications for Professional Counseling and Education

Abstract: With the extreme growth of people who identify as Biracial or Multiracial, it is evident that their unique racial experiences need to be better understood, especially within the field of professional counseling, to underscore competent practice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Research into this anomaly has found that black ethnicity is mislabelled on death certificates [2]. A quote from a participant in a racial mislabelling study stated, ‗If you're not white skin toned, then you're Black' [44]. This may explain why all the statistics are so high; people only use two ethnicities when making calls to the police.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Research into this anomaly has found that black ethnicity is mislabelled on death certificates [2]. A quote from a participant in a racial mislabelling study stated, ‗If you're not white skin toned, then you're Black' [44]. This may explain why all the statistics are so high; people only use two ethnicities when making calls to the police.…”
Section: Findings and Discussionmentioning
confidence: 99%